2021
DOI: 10.5607/en20056
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Comparison of Subcortical Structures in Elderly Subclinical Depression: Structural Analysis with 3T MRI

Abstract: Depression in the elderly population has shown increased likelihood of neurological disorders due to structural changes in the subcortical area. However, further investigation into depression related subcortical changes is needed due to mismatches in structural analysis results between studies as well as scarcities in research regarding subcortical connectivity patterns of subclinical depression populations. This study aims to investigate structural differences in subcortical regions of aged participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Furthermore, a fMRI study of a highly anxious population indicated aberrant connectivity of the left hippocampus and thalamus ( Yang et al, 2019 ). Research has demonstrated that the connectivity between the hippocampus and thalamus affects depression to a large degree ( Im et al, 2021 ). In our study, the thalamus was shown to have enhanced connectivity with the hippocampus, and the enhanced FC values between the two regions were negatively correlated with behavioral performance in rats with SAE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a fMRI study of a highly anxious population indicated aberrant connectivity of the left hippocampus and thalamus ( Yang et al, 2019 ). Research has demonstrated that the connectivity between the hippocampus and thalamus affects depression to a large degree ( Im et al, 2021 ). In our study, the thalamus was shown to have enhanced connectivity with the hippocampus, and the enhanced FC values between the two regions were negatively correlated with behavioral performance in rats with SAE.…”
Section: Discussionmentioning
confidence: 99%